From The Editor - DeNisi, Angelo (Academy of Management Journal, 1996)
The article announces that Mark Huselid's article, “The Impact of Human Resource Management Practices on Turnover, Productivity, and Corporate Financial Performance,” has won the Best Paper Award for 1995. The author also discusses several papers published within the issue including “Why Cross-National Differences in Role Overload? Don't Overlook Ambient Temperature,” by Evert Van De Vliert and Nico W. Van Ypern, and “The Impact of Human Resource Management on Organizational Performance: Progress and Prospects,” by Brian Becker and Barry Gerhart.